DUKUNGAN AYAH DALAM PEMBERIAN AIR SUSU IBU - Dewi Andariya Ningsih (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2018)
Breastfeeding is a natural process to provide the best food in starting a newborn's life. A positive attitude of mothers in playing their primary role in determining the decision to breastfeed and the duration of exclusive breastfeeding is also supported by the importance of the role of Father has been proven in breastfeeding.This study is a literature review (Literature Review) that tries to analyze about the father's milk. Sources for conducting this literature review include a systematic search for a computerized database (Jurnal Oksitosin, Lancet, Journal of Human Lactation, Irish medical journal, Breastfeeding Medicine, Maternal & Child Nutrition, British Journal of Midwifery, Health Promotion International, International Breastfeeding Journal, International Breastfeeding Journal, Indian Pediatrics). Based on some journals there are 5 parts of the study of this article was Knowledge of breast milk, positive attitude to breastfeeding, involvement in decision making process, Practical Support and Emotional Support. Father's role has proven to be an important factor in the mother's decision to start and continue breastfeeding her baby. But the role of Father in that case was rarely done and although the role of Father in decision making is secondary to a mother in terms of breastfeeding, the practical and emotional support given by a father greatly contributes to the success of the exclusive breastfeeding process. Keywords: Breast Milk, Father Support, Breastfeeding ABSTRAK Menyusui adalah proses alamiah untuk memberikan makanan terbaik dalam mengawali kehidupan bayi baru lahir. Sikap positif ibu dalam memainkan peran utamanya dalam menentukan keputusan untuk menyusui dan durasi dalam memberikan ASI ekslusif juga didukung oleh pentingnya peran Ayah telah terbukti dalam pemberian ASI. Studi ini yakni merupakan tinjauan literatur (Literature Review) yang mencoba menganalisis tentang Ayah ASI. Sumber untuk melakukan tinjauan literatur ini meliputi pencarian sistematis database terkomputerisasi (Jurnal Oksitosin, Lancet, Journal of Human Lactation, Irish medical journal, Breastfeeding Medicine, Maternal & Child Nutrition, British Journal of Midwifery, Health Promotion International, International Breastfeeding Journal, International Breastfeeding Journal, Indian Pediatrics). Berdasarkan beberapa jurnal terdapat 5 bagian dari kajian artikel ini yaitu Pengetahuan tentang ASI, Sikap positif untuk menyusui, Keterlibatan dalam proses pengambilan keputusan, Dukungan Praktis dan Dukungan emosional. Peran Ayah telah terbukti menjadi faktor penting dalam keputusan ibu memulai dan terus menyusui bayinya. Tetapi peran Ayah dalam hal tersebut masih jarang dilakukan dan meskipun peran Ayah dalam pengambilan keputusan bersifat sekunder bagi seorang ibu dalam hal menyusui, dukungan praktis dan emosional yang diberikan seorang Ayah sangat membantu suksesnya proses menyusui secara ekslusif. Kata kunci : ASI, Dukungan Ayah, Menyusui